Assessing the Impact of Failure Factor In Term of Preventive Maintenance Planning Adopting Witness Simulation Software - YAR, MUHAMMAD ASFAND (IRC, 2018)
Equipment and system in a work-life industry won't stay safe or dependable if they are not properly maintained. The universal target of maintenance procedure is to utilize the information regarding failure and accidents and to achieve a safe and healthy working environment. The aim of this paper is to provide vital information regarding preventive maintenance (PM) planning. The target is to accomplish the greatest conceivable safety with the low cost. In this research, it proposes an impact of failure appraisal technique for preventive maintenance (PM). Preparing and evaluating of a reliable model for factory systems, generated by using witness simulation, which enables the use of multiple intervals between maintenance interferences. Failure Mode and Effect Analysis (FMEA) approach method will be chosen as a risk assessment in this research work to synthesize the potential failure modes to identify early response and smoothly promote a preventive maintenance planning.